Research on the Influence Mechanism of Platform Corporate Social Responsibility on Customer Extra-Role Behavior - Wenjun Liu; Chenye Wang; Lin Ding; Cuibo Wang (Discrete Dynamics in Nature and Society)
Platform enterprises, which are growing in both quantity and scale, have been inseparable from modern life. In China, the laws specific to platform enterprises fall behind their ever-changing business model. Hence, it is an urgent requirement that platform enterprises undertake their social responsibilities, which will influence consumer extra-role behaviors besides bringing reputation advantages to the enterprises. Based on the motivation theory and social exchange theory, this paper divides corporate social responsibility (CSR) into business ethical responsibility and public welfare responsibility using the CSR division method proposed by McWilliams and Siegel, puts forward self-moral restraint as the proxy variable for business ethical responsibility and explains the relationship between CSR and customer extra-role behavior. It is found that customer extra-role behavior is positively influenced by platform enterprises’ social responsibility. The perception of interest consensus exerts a positive influence on extra-role behavior, so does the perception of service identity. The public welfare responsibility is positively influenced by business ethical responsibility.